INTEGRASI MEDIA DIGITAL DALAM LAYANAN BIMBINGAN DAN KONSELING SEBAGAI STRATEGI PENGUATAN PENDIDIKAN HOLISTIK DI SEKOLAH MENENGAH PERTAMA - Mulyani, Puji; Kusrina, Tity; Kusrina, Suriswo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has implications for changes in educational practices, including the provision of guidance and counseling (BK) services in schools. At the junior high school (SMP) level, students are in the early adolescent phase, characterized by the interconnectedness of academic, social, and emotional development, thus requiring comprehensive and sustainable support services. The use of digital media is considered a relevant strategy to increase the adaptability of guidance and counseling services in accordance with the dynamics of current educational developments. This article aims to conceptually analyze the integration of digital media in guidance and counseling services as an effort to support the strengthening of holistic education in junior high schools. The research uses a literature review method with a conceptual qualitative approach through a review of accredited national journal articles, scientific reference books, and relevant educational policy documents. The results of the analysis indicate that the integration of digital media in BK services has the potential to increase service accessibility, encourage student engagement, and expand the sustainability of counseling support in a preventive and developmental context. However, the implementation of digital media in BK services in schools still tends to be fragmented and has not been systematically integrated within a holistic educational framework. Therefore, this article offers a conceptual framework for digital media integration in guidance and counseling services as a reference for school counselors and educational stakeholders in developing guidance and counseling services that are more contextual and oriented towards the developmental needs of junior high school students.